EMPOWERING WELL-BEING: STRATEGIES FOR ELEVATING HEALTHCARE QUALITY AND BOOSTING HEALTH CONSCIOUSNESS - Mehmas, AL Mutairy, Hind; Mueallath, AL Rashidi, Ahmed; Saleh, AL Ghamdi, Salha; Saad, AL Ghamdi, Abdulmajeed; Fehaid, AL Shammari, Dalal; Omar, AL Otaibi, Khadija (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2023)
The article "Empowering Well-Being: Strategies for Elevating Healthcare Quality and Boosting Health Consciousness" examines the critical components of enhancing healthcare quality and increasing public health awareness. It highlights the importance of understanding healthcare quality, including global standards and benchmarks, and assesses the current state of public health awareness, particularly in the context of misinformation and the influence of social media. The article proposes various strategies to improve healthcare quality, focusing on patient care, technological innovation, and professional training. It also emphasizes the role of educational initiatives, public health campaigns, and media collaboration in raising health consciousness. Additionally, the article presents case studies demonstrating successful models of healthcare improvement and effective health awareness campaigns. It addresses challenges such as financial constraints, cultural factors, and regulatory hurdles, offering insights into overcoming these barriers. The conclusion looks toward the future of healthcare and health awareness, considering the potential impact of AI and digital health. This article serves as a comprehensive resource for healthcare professionals, policymakers, and the general public interested in advancing healthcare quality and health awareness.